The Influence of Education Level, Technology and Regional Original Income on Economic Growth in Districts/Cities of Bali Province - Mutiara Tria Natalia Sitorus; Anak Agung Putu Bagus Widanta (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Bali Province, which is an international tourism destination, must be able to improve its human resources by utilizing technology and allocating stable local revenue. The purpose of this study was to analyze the effect of education level, technology and local revenue on economic growth in the Regency/City of Bali Province, both simultaneously and partially. The data sources used in this study were secondary sources with 45 observation points that combined time series and cross-section data. The results of the study showed that 1) the level of education, technology and local revenue had a positive and significant effect simultaneously on economic growth in the Regency/City of Bali Province, 2) the level of education and local revenue partially had a positive effect on economic growth in the Regency/City of Bali Province, 3) Technology partially had a negative effect on economic growth in the Regency/City of Bali Province. Based on the results of the study, to increase economic growth, investment in human resource development needs to be carried out by increasing access and quality of education for the community, then the local government also needs to evaluate and adjust the technology implementation strategy in order to provide a positive contribution, and finally the local government can optimize sources of local revenue and increase the efficiency of its management.